Evaluation of Transition to Electronic Prescriptions in Turkey: Perspective of Family Physicians - Sinan Bulut; Ahmet Yıldız; Sıdıka Kaya (Kerman University of Medical Sciences, 2019)
Background One of the most important steps of the health transformation program involves the application of electronic prescriptions (e-prescriptions) in health services. Information technologies are highly important in generating e-prescriptions, which can be described as a document produced by authorized personnel electronically, containing written information and instructions regarding a patient's medication and its usage. E-prescribing has become increasingly applied in recent years as a contributing application to prescribers and patients. The aim of this study was to determine the level of satisfaction of family physicians providing primary care in Turkey regarding the application of e-prescriptions, and reveal the related positive effects and problems encountered in the first months of implementation of e-prescribing. Methods A questionnaire with eight questions was sent to e-mails of all family physicians working in Turkey in May 2013. A total of 1564 family physicians filled in the questionnaire form and sent it back by e-mail. The responses to open-ended questions were evaluated by content analysis. Results It was observed that the most frequently indicated advantages of the application of e-prescriptions were speeding up the prescription process and saving time (36.6%). The most commonly reported problems regarding the application of e-prescriptions were found to be system-induced problems (26.5%) and internet problems (19.9%). In addition, the mean score of satisfaction of the family physicians who did not report problems with the application of e-prescriptions was higher than that of those who reported having problems with it. In the study, 77.8% of the family physicians were satisfied with the application of e-prescriptions. Conclusion Although some problems were reported regarding the application of e-prescriptions in the first months of the application, family physicians participated in the study were found to be satisfied with the application of e-prescriptions, and identified positive effects on their work and processes.